Addictive behaviour - Welch, Edward T. 1953-; Shogren, Gary Steven (Grand Rapids, MI Baker, 1995)
Includes bibliographical references.
Keywords: Pastoral counseling; Addicts -- pastoral counseling of; Substance abuse -- religious aspects -- Chrtistianity